(untitled) (Research, Society and Development, 2025)
Introduction: The social distancing imposed to thousands of people’s lives during the COVID-19 pandemic has resulted in various changes on their daily routine, among them, the increase on the usage of screens, especially in the children and teen population. It is also known that the excessive use of these gadgets have consequences on the neurodevelopment. Goal: To assess the impact of the excessive use of eletronic devices on mental health during the pandemic in Sergipe. Methodology: Ecological, discreptive, exploratory and observational study, through the perception of the gardians about the consequences generated by the use of screens through the application of a stadardized questionaire (Google Forms), including sociodemografic, epedemiologic and data. Results: The acquired data show that the increase of screen time, as well as the consequences of its excessive use, like: anxiety symptoms, increase in anger issues, image distortion (body dysmorphia) and learning difficulties. Conclusion: Based on the acquired information it is evident that the COVID-19 pandemic has impacted significantly the abusive use of screens, generating consequences to the mental health of children and teenagers.